Pengaruh Ekstrak Kayu Manis Cinnamomum Burmannii dan Larutan Alkalin Peroksida sebagai Pembersih Basis Gigi Tiruan Nilon Termoplastik terhadap Stabilitas Warna - Dinda Tryana Sembiring (Syntax Corporation Indonesia, 2024)
The background of this study is to evaluate the effect of soaking the base of thermoplastic nylon dentures in cinnamon extract Cinnamomum burmannii and alkaline peroxide solution on color stability, considering the importance of maintaining denture hygiene with safe and effective cleaning agents. This study aimed to evaluate the colour stability of thermoplastic nylon denture bases after immersion in Cinnamomum burmannii 20% cinnamon extract, alkaline peroxide solution, and distilled water for 4 and 8 days. This research is a laboratory experimental research. This study was conducted with Post-Test Only Control Group Design, which is research with treatment on one or more groups whose final results are compared with the control group, that the colour stability of thermoplastic nylon denture bases after immersion in Cinnamomum burmannii 20% cinnamon extract and alkaline peroxide solution had similar mean ΔE unit values, namely 2.45 ΔE ± 0.27 and 2.24 ΔE ± 0.28 for 4 days, and 2.87 ΔE ± 0.19 and 2.58 ΔE ± 0.30 for 8 days. While immersion in distilled water showed lower mean values of ΔE units, namely 1.17 ΔE ± 0.10 and 1.35 ΔE ± 0.29. Statistical test results showed that there was a significant effect on colour stability (p = 0.0001), but there was no significant difference between cinnamon extract and alkaline peroxide solution, either for 4 days (p = 0.192) or 8 days (p = 0.113).